2017
DOI: 10.3390/ijerph15010053
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Maintaining the Mental Health of Employees after the Fukushima Nuclear Disaster: Findings from Companies Located in the Evacuation Area

Abstract: After the nuclear disaster in Fukushima on 11 March 2011, some businesses were permitted to continue operating even though they were located in the evacuation area designated by the Japanese government. The aim of this study was to examine differences in the mental health status, workplace, living environment, and lifestyle of employees in the evacuation and non-evacuation areas. We also investigated factors related to their mental health status. Data for this cross-sectional study were collected from the ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…In contrast, good general subjective health condition and steady physical activities may have promoted mental health recovery among the evacuees and residents. A previous study reported that employees in the evacuation area who had good general subjective health and regular physical activity could maintain their mental health in the post-disaster period even if their work and life circumstances had significantly changed [ 39 ]. In the post disaster period of the Great East Japan Earthquake and Fukushima Daiichi nuclear power plant accident, numerous supports including maintaining the general health and physical activity level among the evacuees and residents have been received health guidance as a part of the disaster health activities [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, good general subjective health condition and steady physical activities may have promoted mental health recovery among the evacuees and residents. A previous study reported that employees in the evacuation area who had good general subjective health and regular physical activity could maintain their mental health in the post-disaster period even if their work and life circumstances had significantly changed [ 39 ]. In the post disaster period of the Great East Japan Earthquake and Fukushima Daiichi nuclear power plant accident, numerous supports including maintaining the general health and physical activity level among the evacuees and residents have been received health guidance as a part of the disaster health activities [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chi-square test and multivariable logistic regression models were used to examine the association of mental health recovery with disaster-related experiences, general health status, and lifestyle, economic status, and social network variables. In particular, two models were analyzed in multivariable logistic regression analysis: Model 1 was adjusted by age, gender, disaster-related experiences, and current economic status, which was observed to affect disaster-associated mental health recovery [ 30 , 34 , 35 ]; and Model 2 had current health status and lifestyle (general subjective health status, sleep quality, physical activity level, and laughing frequency) and social network status added to the variables in Model 1, which could be protective for their mental health [ 24 , 25 , 28 , 36 , 37 , 38 , 39 ], and evacuees received health guidance as a part of disaster health activities [ 40 , 41 , 42 ]. Moreover, the t -test was utilized to assess the K6 scale in the “Recovered” and “Non-recovered” groups.…”
Section: Methodsmentioning
confidence: 99%
“…In order to assess the necessity of further disaster-related mental health activities for evacuees and residents, this study aims to clarify the current statuses of psychological distress, post-traumatic stress, and radiation health anxiety among evacuees who have rebuilt their permanent home after the lifting of evacuation orders, comparing their results with those of the residents who did not evacuate. Moreover, evacuees exhibit effects in terms of their sleeping conditions or drinking behavior due to disaster-related experiences or following drastic lifestyle changes [ 15 , 16 , 17 , 18 ]. Since health anxiety due to radiation exposure has been associated with media utilization in previous studies [ 19 , 20 ], we also investigate media utilization regarding radiation in order to assess the relationship with radiation health anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…They summarized that the governing factors of radiation risk perception included demographics, disaster-related stressors, trusted information, and radiation-related variables; and that the effects of radiation risk perception comprised severe distress, intention to leave employment or not to return home, or other dimensions. Miura et al, Orui et al, Oe et al, Itagaki et al, Suzuki et al, Kuroda et al, and/or Ito et al added new findings to the systematic reviews of Takebayashi et al [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. They demonstrated that the Fukushima disaster imposed various dimensions of insufficient physical activity, inappropriate sleep, and psychological health risks among affected people.…”
mentioning
confidence: 99%
“…In particular, radiation perception and anxiety were strongly associated with other mental disorders, highlighting the unique severity of a nuclear disaster. Orui et al also suggested that those who laughed frequently, had a social network, and felt satisfied with their working and living environments, were more likely to maintain psychiatric stability [ 4 ]. Murakami et al assessed the effects of various radiological countermeasures on subjective well-being and mental health conditions post-disaster.…”
mentioning
confidence: 99%